STRATEGI GURU PENDIDIKAN ANAK USIA DINI DALAM PENERAPAN PEMBELAJARAN STEAM (SCIENCE, TECHNOLOGY, ENGINEERING, ART, AND MATHEMATICS) DI KOTA MALANG - Aprilia, Elok Firdaus (Jurnal Penelitian Anak Usia Dini, 2022)
Learning strategy is a design and activities carried out by teachers and students that include methods and resources to achieve learning objectives. The objectives of this study are to find out the teacher's strategy in the application of STEAM (science, technology, engineering, art, and mathematics) learning and to find out the advantages and disadvantages of its application. This study used a qualitative approach with descriptive research. The subject of this study are three teachers in three early childhood education institutions in Malang, namely KB-TK Permata Iman 3, TK Al-Ghoniyya, and KB-TK Taman Harapan. The data was collected by using the interview method and strengthened with documentation. Data analysis in this study used the Miles and Huberman method. The validity of the research data was tested using triangulation of data sources. The abstract section of Jurnal Penelitian Anak Usia Dini article serves to briefly describe the content of the journal. For journal abstract, it turns out to be over 150 to 250 words which summarizes the focus and significance, methods, results, and conclusions. The writing that should be avoided in writing abstracts is the existence of abbreviations or quotes. Abstract must stand alone without footnotes. and it consists of one paragraph and typed in one space. The abstract is written using Palatino Linotype-10, flattened left and right and spacing between lines 1 space. The research findings conclude that strategy used by early childhood teachers in the application of STEM (science, technology, engineering, art, and mathematics) in Malang is an indirect strategy. The advantages of this learning are increased students' creativity and confidence, while the disadvantages of this learning require a lot of learning materials and media. Strategi pembelajaran merupakan rancangan dan kegiatan yang dilakukan oleh guru dan peserta didik yang mencakup metode dan sumber daya untuk mencapai tujuan pembelajaran. Tujuan dari penelitian ini yaitu untuk mengetahui strategi yang digunakan guru dalam menerapkan pembelajaran STEAM (science, technology, engineering, art, and mathematics), serta mengetahui kelebihan dan kekurangan dalam penerapannya. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian deskriptif. subjek penelitian ini yaitu 3 guru di 3 lembaga pendidikan anak usia dini di Kota Malang yaitu KB-TK Permata Iman 3, TK Al-Ghoniyya dan KB-TK Taman Harapan. Data dikumpulkan dengan metode wawancara dan diperkuat dengan dokumentasi. Analisis data pada penelitian ini menggunakan metode Milles dan Huberman. Data penelitian diuji keabsahannya menggunakan triangulasi sumber data. Hasil penelitian dapat disimpulkan bahwa strategi yang digunakan guru pendidikan anak usia dini dalam penerapan pembelajaran STEAM (science, technology, engineering, art, and mathematics) di kota Malang menggunakan strategi tidak langsung. Kelebihan dari penerapan pembelajaran ini yaitu meningkatkan kreativitas dan meningkatkan percaya diri anak, sedangkan kekurangan dari pembelajaran ini yaitu memerlukan banyak bahan dan media pembelajaran.